School’s Perspectives on Educational Programmes under Corporate Social Responsibility Initiatives. Case Study: Malaysia - Athirah, Azhar; Azlinda, Azman (The International Academic Forum (IAFOR), 2021)
This study explores the impacts of the Corporate Social Responsibility educational programme from the schools’ perspectives towards their pupils and school. A qualitative approach was chosen from a case study of these programmes conducted in Malaysia. The method used for data collection was semi-structured interviews. Purposive sampling was adopted to collect data from headmasters/mistresses from 10 primary schools and was analysed using narrative analysis. Findings shows that these programmes have impacted pupils through educational exposure, a holistic approach, academic improvement, feeling motivated, encouraging creativity and assisting in pupils’ future career development. One of the impacts that were related to the educational programmes was the teaching and learning knowledge that was gained by the teachers. Other than that, the educational programmes also eased the financial burden of the school as well as providing benefits to the surrounding community. Schools suggested that the programmes should be improved by creating better and more programme type content, being more academically focused, allocating more funding, being conducted over a longer period for sustainability, and conducting the programme more regularly. Corporate Social Responsibility educational programmes in future are suggested to be academic related which should include an English language programme, information technology, 21st century learning, a green programme, basic skills (read, write, count), a motivational programme, and a study visit. In conclusion, CSR educational programmes initiatives must be sustainable because it had great impact on pupils, teachers, schools, and the community surrounding the school.